Model Inquiry learning Berbantuan Media PhET Sebagai Virtual Laboratory Terhadap Keterampilan Proses Sains Siswa SD - Vannilia, Vannilia; Fanani, Achmad; Rosidah, Cholifah Tur (EDUPEDIA Publisher, 2023)
This research is motivated by a problem of low science process skills. The purpose of this stud is to find out whether there is an influence on the use of the Inquiry learning model assisted by PhET media as a Virtual Laboratory on students' science process skills on class IV energy transformation material at SDN Dukuh Menanggal 1/ 424 Surabaya. This type of research is a Quasi-Experimental Design experimental research with a Post-test Only Control Group Design research design. The sample of this study was class IV B totaling 25 people as a control class and class IV C totaling 24 people as an experimental class. The sampling technique used purposive sampling technique. Research data were obtained using science process skills test sheets. From the results of the t-test, it shows that the results of the study of Sig. (2 tailed) (0.00) values < 0.05 which means that H0 is rejected and Ha is accepted. It can be concluded that the Inquiry learning model assisted by PhET media as a Virtual Laboratory affects the science process skills of students of SDN Dukuh Menanggal 1/424 Surabaya.